Political Public Relations Campaign for Election of Mayor and Deputy Mayor of Solok Period 2016-2020 Division Project Officer - feby mangireta .; Agus Naryoso . (Interaksi Online, 2016)
This thesis field work is Political Public Relation Campaign in the Election of Mayor and Deputy Mayor of Solok Period 2016-2021. This thesis work was made by the Public Relations team under the guidance of Mr. Agus Naryoso, S.sos, M.si Department of Communication Studies Program Strata 1 (S1), Communication Science Diponegoro University. This thesis field works aimed to win a political party teams Irzal Ilyas H. and H. ALfauzi Bote known as “Kita Sahabat Imam” Campaign, in the election of mayors and deputy mayor of Solok using public relations. Public relation political campaign strategy used in “Kita Sahabat Imam” Campaign is event, blusukan, community relations, third party endorser, and digital public relations. The final evaluation in this thesis works indicates that the PR campaign strategies were implemented successfully because it reaches all the indicator needed. The major constraint was the black campaign strategy from the other rival party. Suggestion for the futher works / research in this field are, a more comprehensive understanding about political strategy “Kita Sahabat Imam” campaign. It needed more research in volving the study of various disciplines, such as Psychology and Law.